2006
DOI: 10.1007/s10029-006-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical study of laparoscopic treatment of incisional and ventral hernia using a composite mesh: indications, complications and results

Abstract: The aim of this study is to establish the indications, safety, efficacy, feasibility and reproducibility of the laparoscopic technique in treating defects in the abdominal wall, including those of large dimensions, to standardise the surgical technique and to confirm the performance of the composite prosthesis used (Parietex, Sofradim). The study encompassed the period from January 2001 to December 2004 and included 178 nonselected patients (108 women and 70 men), with an average age of 56 years (range: 26-77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 17 publications
2
40
0
12
Order By: Relevance
“…Comparable single-institution case series and one multicentre randomised study reported recurrence rates as low as 0-2.5%, [18][19][20][21][22] whereas prospective national registries have suggested much higher recurrence rates of 15.5% at a median of 21 months follow up. 6 Other contributing factors for recurrence of hernia include the number and size of the defects, difficulty of dissection, mesh fixation technique and operation.…”
Section: Discussionmentioning
confidence: 96%
“…Comparable single-institution case series and one multicentre randomised study reported recurrence rates as low as 0-2.5%, [18][19][20][21][22] whereas prospective national registries have suggested much higher recurrence rates of 15.5% at a median of 21 months follow up. 6 Other contributing factors for recurrence of hernia include the number and size of the defects, difficulty of dissection, mesh fixation technique and operation.…”
Section: Discussionmentioning
confidence: 96%
“…19,20 It is also worth observing that while in the past recurrence of inguinal hernia was an important postoperative complication, after the advent of the tension-free mesh technique the risk of recurrence has decreased considerably and the current incidence rates are as low as 1-4%. 14,85 Cost-effectiveness…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…While evolved immensely, especially over the last few decades. Recurrence of inguinal hernia was initially a significant problem; however with the advent of the tension-free mesh repair as described as Lichtenstein Repair (LR) [30], recurrence rate has consistently been reported as low as 1-4% [31][32][33][34], a drop from up to 50-60%. …”
Section: Resultsmentioning
confidence: 99%